Into the void: a review of postoperative urinary retention after minimally invasive gynecologic surgery. Issue 4 (August 2018) - Wong, Marron C.; Isaacson, Keith; Morris, Stephanie
Abstract : Purpose of review: Postoperative urinary retention (POUR) is a common occurrence after minimally invasive gynecologic surgery (MIGS). This review discusses the definition, incidence, evaluation, diagnosis, and treatment of POUR after MIGS. Recent findings: Reported incidence of POUR after MIGS ranges from 0.5 to 21%. Active void trials or awaiting spontaneous void after surgery are both viable options for diagnosing POUR, but active void trials appear to be more accurate, quicker, and preferred by patients. The use of enhanced recovery after surgery pathways and minimizing postoperative opioids can help reduce POUR. Summary: It is important to evaluate postoperative patients for POUR after MIGS. Standard guidelines are lacking for the evaluation and treatment of patients with POUR.